Magical Realism Depicted in A Space For The Unbound (2023) Game - Rifqi, Ahmad Zidan (LITERA KULTURA : Journal of Literary and Cultural Studies, 2025)
This study analyses the depiction of magical realism in A Space For The Unbound (2023), a video game developed by Mojiken Studio. The research applies Wendy B. Faris’s framework on magical realism, focusing on its five key characteristics: irreducible elements, the phenomenal world, unsettling doubts, merging realms, and disruption of time, space, and identity. The study conducts a narrative analysis of the game, revealing how these characteristics shape the narrative structure. The findings suggest that the game integrates supernatural elements not only as a stylistic device but also as a tool to engage players emotionally and challenge conventional storytelling. Through the experiences of the protagonists, Atma and Raya, the game uses the supernatural to address themes of trauma, identity, and mental health within a culturally rich, rural Indonesian context. The analysis shows that A Space For The Unbound blurs the boundaries between reality and the fantastical, creating an immersive narrative experience that goes beyond traditional linear storytelling. The research highlights the potential of magical realism in interactive media, offering new insights into the emotional depth and narrative innovation in video games.